Reduced intensity versus myeloablative conditioning for MDS: long-term results of an EBMT phase III study (RICMAC) - Niederwieser, Christian; Iacobelli, Simona; Franke, Georg-Nikolaus; Koster, Linda; van Os, Marleen; Platzbecker, Uwe; Hübel, Kai; Scheid, Christoph; Müller, Lutz P.; Stelljes, Matthias; Morozova, Elena; Passweg, Jakob R.; et al. (Bone marrow transplantation, 2024)
Short-term outcome of myeloablative (MAC) and reduced intensity (RIC) conditioning in the prospective randomized international EBMT RICMAC study in patients with myelodyplastic syndrome (MDS) was comparable but longer follow up is lacking. Patients with MDS aged 18-65 years were randomized to receive MAC (N = 64) with busulfan/cyclophosphamide or RIC (n = 65) with busulfan/fludarabine followed by stem cell transplantation -(HCT) from HLA matched or mismatched donor. After a median follow-up of 6.2 (0.4-12.5) years, 10-year OS and RFS were 54.0% and 43.9% for RIC and 44.4% and 44.2% for MAC (p = 0.15 and p = 0.78), respectively. Since the first report, 6 patients died on NRM, 4 after RIC, and 2 after MAC. Similarly, 8 patients relapsed (4 in each arm), increasing the number of relapsed patients to 28. The second HCT was performed in 18 pts, 8 in the MAC, and 10 in the RIC arm. In a multivariate analysis, ECOG status and chemotherapy prior to HCT were independent risk factors for OS and RFS, ECOG and low cytogenetic risk for NRM and chemotherapy prior to HCT for RI. Patients with low cytogenetic risk had better OS [p = 0.002], RFS [p = 0.02], and NRM (p = 0.015) after RIC as compared to MAC.